Callisto's Atmosphere and Its Space Environment: Prospects for the Particle Environment Package on Board JUICE. Issue 5 (13th May 2022) - Galli, A.; Vorburger, A.; Carberry Mogan, S. R.; Roussos, E.; Stenberg Wieser, G.; Wurz, P.; Föhn, M.; Krupp, N.; Fränz, M.; Barabash, S.; Futaana, Y.; Brandt, P. C.; et al.
Abstract: The JUpiter ICy moons Explorer (JUICE) of the European Space Agency will investigate Jupiter and its icy moons Europa, Ganymede, and Callisto, with the aim to better understand the origin and evolution of our Solar System and the emergence of habitable worlds around gas giants. The Particle Environment Package (PEP) on board JUICE is designed to measure neutrals and ions and electrons at thermal, suprathermal, and radiation belt energies (eV to MeV). In the vicinity of Callisto, PEP will characterize the plasma environment, the outer parts of Callisto's atmosphere and ionosphere and their interaction with Jupiter's dynamic magnetosphere. Roughly 20 Callisto flybys with closest approaches between 200 and 5, 000 km altitude are planned over the course of the JUICE mission. In this article, we review the state of the art regarding Callisto's ambient environment and magnetospheric interaction with recent modeling efforts for Callisto's atmosphere and ionosphere. Based on this review, we identify science opportunities for the PEP observations to optimize scientific insight gained from the foreseen JUICE flybys. These considerations will inform both science operation planning of PEP and JUICE and they will guide future model development for Callisto's atmosphere, ionosphere, and their interaction with the plasma environment. Key Points: Particle Environment Package (PEP) on JUpiter ICy moons Explorer (JUICE) will provide in situ and remote measurements of Callisto's atmosphere and its space environment during ∼20 flybys We investigate operation plans and instrument capabilities to optimize science return from PEP observations The interactions of the atmosphere with the space environment and surface are complex and must be further analyzed in preparation for JUICE